The work intensity of wheelchair badminton match - Nagashima, O.; Warashina, Y. (The Journal of Physical Fitness and Sports Medicine, 2017)
Wheelchair badminton (a part of Sport Classes in para-badminton) will be an official sport for the first time at the Tokyo 2020 Paralympic Games. Improving the skills and enhancing training programs are required, however, the work intensity of wheelchair badminton during the matches has not been revealed. [Aims] To reveal the exercise pattern and the intensity of wheelchair badminton by the game analysis and measuring heart rate. [Methods] Elapsed time from the service until the shuttlecock hit the ground is defined as rally time, and elapsed time from then to the next service is defined as rest time. By analyzing the singles matches at international competitions, we calculated average rally time, rest time and shot interval. Heart rate (HR) was recorded every 1 s throughout the match by H7 sensor (Polar), and the maximum and the average HR were calculated. [Results] Rally time was 7.5-7.8 seconds, and rest time was 13.1-13.5 seconds. There seems no great distinction between wheelchair badminton and abled badminton. On the other hand, shot interval was 1.2-1.3 seconds, which was significantly shorter than abled badminton (less than 1 s). The average HR was 172-175 bpm, and the maximum HR was 194-197 bpm. These results suggest wheelchair badminton is high intensity exercise. Although wheelchair badminton is intermittent exercise which repeats rally and rest, HR did not decrease during the rest time. [Conclusions] Wheelchair badminton is required high intensity intermittent exercise which repeats rally and rest.